Policies for controlling the covid-19 pandemic through social media communications by the East Kalimantan provincial government - Irawan, Bambang (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
During the Covid-19 outbreak, social media became the home for all sources of information for the use of social media due to limited public activities outside. Social media can be used well with innovation and information conveyed to the public; the public uses social media as a general information channel, especially Twitter. This study aims to find information related to the Covid-19 pandemic control policy through social media communication by the East Kalimantan Provincial Government. This study uses a qualitative method, QDA Miner or qualitative data analysis miner Nvivo 12 Plus, which analyzes content, network, and word cloud. The two Twitter accounts that are the source of data in this study are the official account of the Provincial Government of East Kalimantan @Pemprov_Kaltim, and the official account of the Office of Communication and Information Province East Kalimantan @Kominfokaltim. The findings of this study indicate that the Twitter social media account of the East Kalimantan Provincial Government has a function as a crisis mitigation and management tool. Twitter's social media account with high intensity is the @kominfokaltim account with a difference in the number of tweets that is not much different from the @Pemprov_Kaltim account and the monthly Twitter intensity of the @kominfokaltim Twitter social media account, which is more intense every month in providing information. Information content based on analysis using Nvivo 12 Plus shows that the information conveyed during the Covid-19 outbreak is directly related to policies for handling and growing Covid-19 cases in East Kalimantan.